Grigorije Camblak’s Description of the Construction of the Dečani Church: Its Features and Models - Gavrilović, Anđela Đ. (Collection of Papers of the Faculty of Philosophy in Priština, 2023)
In describing the life and deeds of Serbian Holy King Stefan of Dečani (1322–1331), the author of the second biography of the Serbian king and abbot of the Dečani Monastery, Grigorije Camblak (c.1364–1419/1420) gives an account of the construction of the Holy King’s endowment dedicated to Christ Pantokrator (Fig. 1, 2). He describes in detail the way in which the marble blocks of the church were carved with great skill, prepared and perfectly inserted into the overall structure of the building. He states, “...and the stones are wonderfully and most artfully joined together, so that it seems as if the face of the whole church is one stone wonderfully joined together with skill, so that it seems as if one piece of stone, appearing in an unspeakable beauty…since it is a perfectly carved stone and testifies to the dignity of those who created it” (Цамблак, 1936, p. 23; Трифуновић, 1985, p. 183). The paper notes that the quoted description of the church construction emphatically represents learned ancient literary topos used to describe the most representative architectural monuments, especially those made of marble and deals with the origin and tradition of this specific way of describing the building construction.
Keywords: Dečani Monastery; architecture; description; construction; Grigorije Camblak; ancient topos